2017
DOI: 10.3389/fphy.2017.00030
|View full text |Cite
|
Sign up to set email alerts
|

The Physics of Teams: Interdependence, Measurable Entropy, and Computational Emotion

Abstract: Most of the social sciences, including psychology, economics, and subjective social network theory, are modeled on the individual, leaving the field not only a-theoretical, but also inapplicable to a physics of hybrid teams, where hybrid refers to arbitrarily combining humans, machines, and robots into a team to perform a dedicated mission (e.g., military, business, entertainment) or to solve a targeted problem (e.g., with scientists, engineers, entrepreneurs). As a common social science practice, the ingredie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
2
28
1
Order By: Relevance
“…Again, we assumed that the more redundant were the members, but now of a military team, the poorer the team would perform. With Kullback–Leibler divergence again, we obtained results that were significantly in agreement with our first study, reaffirming its findings [ 44 ]: that is, we found that the more freedom in a nation, the smaller the size of its military measured by its number of military personnel. In addition, we extended our research by hypothesizing and finding that redundancy was significantly associated with the level of corruption in a country, and that the interdependence in a nation’s teams was significantly associated with the individual freedom and the free-market scores of a nation.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Again, we assumed that the more redundant were the members, but now of a military team, the poorer the team would perform. With Kullback–Leibler divergence again, we obtained results that were significantly in agreement with our first study, reaffirming its findings [ 44 ]: that is, we found that the more freedom in a nation, the smaller the size of its military measured by its number of military personnel. In addition, we extended our research by hypothesizing and finding that redundancy was significantly associated with the level of corruption in a country, and that the interdependence in a nation’s teams was significantly associated with the individual freedom and the free-market scores of a nation.…”
Section: Introductionsupporting
confidence: 90%
“…Third, Kelley [ 96 ] found that, in the laboratory, the preferences determined by questionnaires for an individual when alone do not match what an individual choses in a social (game) situation, possibly the rational choice theory’s motivation to impute values based strictly on observations. For the prisoners dilemma game (PDG), no matter what Kelley tried in the laboratory for identifying the strongest preferences of individuals, interdependence transformed the actual choices that they made, impeding game theory from scaling to teams or larger collectives [ 8 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Let it be observed that cycling competition is a different matter: even though (it seems that) a cyclist race is won by only one individual, it is well known that this is a team activity [6,7,8] as usually recognized by the winner in interviews. The to-be-agent-based-model should use ideas based on cooperation beside competition [9,10,11,12,13], -a quite open and intense field of research in "new statistical physics".…”
mentioning
confidence: 99%